A review of the cicada genus Haphsa Distant, 1905 with the description of one new species from China (Hemiptera: Cicadidae) and a phylogenetic analysis of Haphsa and its allies - Wang, Siyue; Peng, Xiaodong; Wei, Cong (Zootaxa, 2021)
The cicada genus Haphsa Distant, 1905 was reviewed based on the description of one new species (Haphsa acutipetala sp. n.) from China and phylogenetic analysis of Haphsa and its allies. The phylogeny of six species of Haphsa and partial related species of Changa Lee, 2016, Sinosemia Matsumura, 1927 and Sinotympana Lee, 2009 was constructed based on COI sequences to understand better the phylogeny of Haphsa and related taxa. Sinosemia Matsumura, 1927 syn. n., Changa Lee, 2016 syn. n. and Sinotympana Lee, 2009 syn. n. are recognized to be new synonyms of Haphsa. Sinosemia shirakii Matsumura, 1927, Changa jsguillotsi (Boulard, 2005), Changa sita (Distant, 1881), Sinotympana incomparabilis Lee, 2009 and Sinotympana caobangensis Pham & Sanborn, 2019 are transferred to Haphsa to become Haphsa shirakii (Matsumura, 1927) comb. n., Haphsa jsguillotsi (Boulard, 2005) comb. rev., Haphsa sita (Distant, 1881) comb. n., Haphsa incomparabilis (Lee, 2009) comb. n. and Haphsa caobangensis (Pham & Sanborn, 2019) comb. n., respectively. A key to species of Haphsa is provided.